Enhancing Critical Thinking and Creativity: The Impact of Tri Kaya Parisudha-Based Metaphorical Thinking in Elementary Education - I Komang Andi Suryawan Andi Suryawan; I Gede Astawan; Gusti Ayu Putu Sukma Trisna (Universitas Pendidikan Ganesha, 2024)
Students' low critical thinking skills and creativity are often caused by conventional learning that does not involve in-depth exploration of concepts. This study aims to analyze and test the influence of the Metaphorical Thinking approach based on Tri Kaya Parisudha on the critical thinking skills and creativity of elementary school students. This study uses a quasi-experimental design with a nonequivalent pre-test post-test control group design pattern. The subjects of the study were grade IV students who were selected through cluster random sampling techniques. Data collection was carried out using validated critical thinking and creativity skills test instruments, while data analysis was carried out using the Multivariate Analysis of Variance (MANOVA) technique which was processed with the help of IBM SPSS 30.0 for Windows software. The results of the analysis showed a significant difference between the experimental group and the control group. Students in the experimental class showed a higher average increase in critical thinking and creativity scores than students in the control class. The significance value of the MANOVA results of 0.000 (p < 0.05) indicates that the Metaphorical Thinking approach based on Tri Kaya Parisudha has a significant effect on improving students' critical thinking skills and creativity. These findings suggest that the integration of local values in innovative learning approaches can be an effective strategy in improving the quality of 21st century learning.